2012
DOI: 10.1016/j.bbalip.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The retinoid X receptors and their ligands

Abstract: This chapter presents an overview of the current status of studies on the structural and molecular biology of the retinoid X receptor subtypes α, β, and γ (RXRs, NR2B1–3), their nuclear and cytoplasmic functions, post-transcriptional processing, and recently reported ligands. Points of interest are the different changes in the ligand-binding pocket induced by variously shaped agonists, the communication of the ligand–bound pocket with the coactivator binding surface and the heterodimerization interface, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
336
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(343 citation statements)
references
References 249 publications
2
336
0
5
Order By: Relevance
“…RXRα is a member of the class II nuclear hormone receptors, and typically acts either as a homodimer or, more commonly, as a heterodimer with other members of this group including the retinoic acid receptors (RARs), the vitamin D receptor VDR, the thyroid hormone receptor TR, liver X receptors (LXRs) and peroxisome proliferator-activated receptors (PPARs) (Dawson and Xia 2012). This important study revealed IGFBP-3 as a potential transcriptional regulator, activating effects mediated through the RXR response element but inhibiting signaling through the RAR response element (RARE, activated by ligand binding to RXR-RAR heterodimers) (Liu et al 2000).…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…RXRα is a member of the class II nuclear hormone receptors, and typically acts either as a homodimer or, more commonly, as a heterodimer with other members of this group including the retinoic acid receptors (RARs), the vitamin D receptor VDR, the thyroid hormone receptor TR, liver X receptors (LXRs) and peroxisome proliferator-activated receptors (PPARs) (Dawson and Xia 2012). This important study revealed IGFBP-3 as a potential transcriptional regulator, activating effects mediated through the RXR response element but inhibiting signaling through the RAR response element (RARE, activated by ligand binding to RXR-RAR heterodimers) (Liu et al 2000).…”
Section: Nuclear Hormone Receptorsmentioning
confidence: 99%
“…Indeed, RXR ligands together with RAR ligands have potential therapeutic value in a variety of immunological and neurodegenerative disorders. [8][9][10] Many synthetic RXR-selective agonists have been reported, 4,5) and diarylamine-type ligands, such as PA024, show very potent activity.11) Therefore, building on the structures of our previously developed potent and subtype-selective RAR agonists, in the present work we synthesized a series of diarylamine ligands incorporating a tricyclic hydrophobic moiety, i.e., hexahydrophenalene or octahydrobenzoheptalene, as candidate RXR agonists. The target compounds were synthesized as follows.…”
mentioning
confidence: 99%
“…This is of interest, because few RXR subtype-selective ligands have been developed. 4,5) These compounds do not show any activity towards RARs even at concentrations above 1000 nM, and are thus activators of RXRs. Dose-response curves of representative compounds are shown in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations